‘I write what I like’ – The Trantraal brothers share their love for their craft – Part 2 - Naidoo, Kareesha (WritingThreeSixty, 2018)
WritingThreeSixty got the wonderful opportunity to interview Nathan and André Trantraal about their writing process, advice to aspiring writers and how they truly feel about J.M. Coetzee.